Radiation Recall Pneumonitis After Treatment With Checkpoint Blockade Immunotherapy: A Case Series and Review of Literature - Riviere, Paul; Sumner, Whitney; Cornell, Mariel; Sandhu, Ajay; Murphy, James D.; Hattangadi-Gluth, Jona; Bruggeman, Andrew; Kim, Sangwoo S.; Randall, J. Michael; Sharabi, Andrew B. (Frontiers in Oncology, 2021)
Background: Radiation recall pneumonitis (RRP) is a poorly understood clinical syndrome in which patients develop radiation pneumonitis triggered by a systemic agent, often years the completion of radiation therapy. Checkpoint blockade immunotherapies have only recently been posited as a trigger for RRP. Here, we present three cases of immunotherapy-induced RRP. Case presentation: Our first patient was diagnosed with primary lung adenocarcinoma, and 4.5 years after completing radiation therapy developed symptomatic RRP immediately following a second dose of nivolumab-containing immunotherapy regimen. Our second patient was diagnosed with primary bladder cancer metastatic to the mediastinum, which was treated twice with radiation therapy. He developed RRP in the days following his second course of ipilimumab-pembrolizumab, and subsequent to a second round of radiation therapy without complication. Our final patient was diagnosed with metastatic small cell lung cancer and received local consolidative radiation therapy in addition to whole-brain radiation. He developed RRP on the 11th day after concluding his 4th cycle of nivolumab-ipilimumab, approximately 7 months after having had completed chest radiation therapy. Conclusions: Immunotherapy-induced RRP is a rare diagnosis which can present more focally than traditional immunotherapy pneumonitis and which must be clinically differentiated from other local processes such as pneumonia. Further research should explore the mechanisms underlying these radiation recall reactions as many patients receive radiation and immunotherapy during the course of their cancer treatment.